Corporate Defendants and the Protections of Criminal Procedure: An Economic Analysis - Khanna, Vikramaditya S. (2004)
Corporations are frequently treated as “persons” under the law. One of the fundamental questions associated with this treatment is whether corporations should receive the same Constitutional protections and guarantees as natural persons. In particular, should corporations receive the Constitutional protections of Criminal Procedure? After all, corporations cannot be sent to jail so the sanctions they face are essentially the same as in civil proceedings. If so, then why not have the same procedural protections for corporate defendants in civil and criminal cases? Little scholarly analysis has focused on this issue from an economic perspective and this article aims to fill that gap. My analysis concludes that the concerns animating most procedural protections in the corporate context (i.e., reducing the costs of adjudicative errors and abusive prosecutorial behavior) would require procedural protections that differ for corporate defendants depending on the identity of the moving party (e.g., government or private litigant), and the type of sanction the corporation is facing, but not on the type of proceedings (criminal or civil) against the corporation. The analysis thus calls for a reorientation of procedural protections for corporate defendants along these lines rather than on the current criminal – civil dichotomy. The implications of such a reorientation are sketched in this paper and may, at times, suggest having stronger protections for corporations in civil proceedings than in criminal proceedings